Weak-phase composite ceramic toughened ultra-low carbon layer long-life stopper rod and preparation method thereof

The multi-layer gradient composite structure formed by the embedded multi-layer gradient composite process solves the problem of deterioration of corrosion resistance caused by carbon dissolution of the plug rod head, and achieves high corrosion resistance and thermal shock resistance of the plug rod, extends the service life and meets the production needs of long pouring.

CN119797945AActive Publication Date: 2025-04-11DONGFANG JUYE HIGHER CERAMIC ANSHAN CITY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411993291.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the steel pouring process, the existing plug rod heads have loose and porous tissues due to carbon dissolution, and the steel penetrates into and reacts with the material, resulting in a degradation of corrosion resistance and unstable control flow, making it difficult to meet the production needs of long pouring.

Method used

The embedded multi-layer gradient composite process is adopted to form a multi-layer gradient composite structure with a lightweight porous partition layer, a rod support layer and an ultra-low carbon erosion-resistant layer. By combining weak combinations, the interface structure stress is eliminated and the corrosion resistance and thermal shock resistance are improved.

Benefits of technology

It significantly improves the corrosion resistance and thermal shock resistance of the plug rod head, reduces cracks and peeling problems caused by interface structural stress, extends the service life of the plug rod, and meets the production needs of long castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797945A_ABST
    Figure CN119797945A_ABST
Patent Text Reader

Abstract

The invention relates to a weak-phase composite ceramic toughening type ultra-low carbon layer long-life stopper rod and a production method. A rod head part of the long-life stopper rod is of a composite structure composed of a stopper rod body, a light porous separation layer and an ultra-low carbon anti-erosion layer. The stopper rod body is made of aluminum carbon materials, and the rod head is of a cone structure. The light porous separation layer is of a conical cap-shaped structure matched with the rod head part and is made of a light porous material; the ultra-low carbon anti-erosion layer is of a conical cap-shaped structure matched with the light porous separation layer and is made of an ultra-low carbon magnesium-rich spinel material with a high-temperature ceramic phase. According to the invention, a pre-embedded multi-layer gradient composite process is adopted, so that the erosion resistance of the rod head is improved, the good thermal shock resistance is also considered, and the problems of thermal shock cracks and peeling of the ultra-low carbon composite layer caused by interface structure stress generated by direct combination in the use process of the stopper rod are solved; and the production requirements of long-casting-time continuous casting production and high-erosivity variety steel are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer and a preparation method thereof. Background Art

[0002] Functional refractory components such as integral stopper rod, long nozzle (for large ladle) and submerged nozzle (for medium ladle) are collectively referred to as the three major parts of continuous casting. The three major parts of continuous casting are essential key materials to ensure the normal production of continuous casting. They connect the ladle, tundish and crystallizer in a trinity, which not only realizes the flow control and diversion of molten steel, but also prevents the secondary oxidation of molten steel, providing an important guarantee for the efficient production of high-quality, high-value-added clean steel. Among them, the main function of the stopper rod is to control the amount of molten steel flowing from the tundish into the crystallizer, maintain the stability of the crystallizer liquid level, and prevent excessive fluctuations in the liquid level. The stopper rod cannot be replaced during the continuous casting production process, so the stability of its quality directly restricts the continuity of steel casting production and the casting time.

[0003] During the steel pouring process, the stopper rod head is in the high-speed flowing molten steel and is always subjected to strong erosion and thermal shock from the molten steel. It is generally believed that the erosion mechanism of the rod head is that the carbon dissolution in the flow control part of the rod head destroys the carbon network structure of the rod head material, making the rod head structure gradually loose and porous, and the molten steel penetrates into the rod head material and reacts with the rod head material, which eventually causes the rod head to gradually deteriorate or peel off, thus seriously affecting the erosion resistance of the rod head. In particular, there is always a negative pressure in the flow control area where the rod head and the bowl mouth cooperate, which accelerates the positive progress of the carbon dissolution mechanism. For the stopper rod made of the same material as a whole, on the one hand, if the carbon content of the rod head is low, its erosion resistance is strong, but its thermal shock resistance is poor, and it is easy to burst and peel off when it contacts with molten steel at the initial stage of continuous casting, resulting in a failure of pouring; on the other hand, if the carbon content of the rod head is high, its thermal shock resistance is good, but its carbon melting loss is fast, resulting in a decrease in the erosion resistance of the rod head and unstable flow control, and the service life of the stopper rod is difficult to meet the use requirements. Therefore, how to balance the erosion resistance and thermal shock resistance of the stopper rod head is a technical difficulty that restricts the service life of the stopper rod.

[0004] At present, the head of the stopper rod is usually made of aluminum carbon, aluminum magnesium carbon or zirconium carbon materials with a carbon content of 9% to 16%. Due to its high carbon content, in the later stage of steel pouring, the phenomenon of forced interruption of steel pouring often occurs due to severe erosion of the rod head and failure of flow control, which makes it difficult to meet the growing long pouring production needs of continuous casting. In order to improve the erosion resistance of the rod head and have good thermal shock resistance, some manufacturers adopt a structure of directly compounding a layer of low-carbon functional layer on the outside of the flow control area of ​​the rod head. The thickness of the low-carbon functional layer is between 7mm and 18mm, and the carbon content is between 5% and 8%. However, this direct compounding method has a strong bonding interface. Since the materials of the inner and outer parts, namely the rod body and the low-carbon functional layer, have great differences in thermal expansion properties, a large bonding stress is generated at the composite interface. Structural stress cracks and thermal shock peeling problems are prone to occur during production and use, making it difficult to produce high-performance and long-life stopper rods with stable quality. Summary of the invention

[0005] The present invention provides a weak-phase composite ceramic toughened ultra-low carbon layer long-life stopper rod and a production method thereof. A pre-buried multi-layer gradient composite process is adopted to form a multi-layer gradient composite structure of a lightweight porous separation layer, a rod body support layer and an ultra-low carbon anti-erosion layer, which improves the erosion resistance of the rod head while taking into account good thermal shock resistance, solves the problem of thermal shock cracks and spalling of the ultra-low carbon composite layer caused by interface structural stress generated by direct bonding during the use of the stopper rod, and meets the production needs of long-casting continuous casting production and production of steel varieties with strong erosion resistance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer, the rod head portion of the long-life stopper rod is a composite structure consisting of a stopper rod body, a lightweight porous separation layer and an ultra-low carbon anti-erosion layer; the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are arranged on the outside of the rod head of the stopper rod body in sequence from the inside to the outside, and the stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are integrally formed by pressure; the stopper rod body is made of aluminum carbon material, and the rod head is divided into a cone structure; the lightweight porous separation layer is a cone-cap shaped structure matched with the rod head portion, and is made of a lightweight porous material; the ultra-low carbon anti-erosion layer is a cone-cap shaped structure matched with the lightweight porous separation layer, and is made of an ultra-low carbon magnesium-rich spinel material with a high-temperature ceramic phase.

[0008] The lightweight porous separation layer has a thickness of 2 to 5 mm and a height of 30 to 60 mm.

[0009] The ultra-low carbon anti-erosion layer has a thickness of 6 to 12 mm and a height of 50 to 90 mm.

[0010] The lightweight porous separation layer is made of low-expansion lightweight hollow sphere material, and is composed of the following raw materials by mass percentage: 81% to 90% lightweight spinel hollow spheres, 2% to 4% graphite, 1% to 5% ceramic powder, 1% to 3% metal silicon powder, and 3% to 7% polypropylene fine powder; in addition, liquid phenolic resin accounts for 3% to 6% of the total mass of the raw materials.

[0011] The particle size composition of the lightweight spinel hollow spheres is 50% to 70% by mass of 0.5 to 0.3 mm and 30% to 50% by mass of 0.3 to 0 mm, and the alumina content is ≥75%; the graphite uses 598 flake graphite powder with a particle size of 30 to 50 meshes and a carbon content of ≥98%; the particle size of the ceramic powder is 200 mesh to 0; the particle size of the metal silicon powder is 200 mesh to 0; and the particle size of the polypropylene fine powder is 120 mesh to 0.

[0012] The raw materials of the ultra-low carbon anti-erosion layer are composed of fused magnesium-rich spinel and a high-temperature ceramic phase former, with liquid phenolic resin added; in terms of mass percentage, the fused magnesium-rich spinel accounts for 70% to 88%; the high-temperature ceramic phase former includes: 3% to 6% magnesium-aluminum spinel powder, 2% to 5% calcined alumina, 1% to 3% titanium dioxide, 1% to 3% cerium oxide, 3% to 5% graphite, 1% to 3% silicon nitride, 1% to 4% metallic silicon powder, and 0% to 1% boron carbide; the liquid phenolic resin accounts for 4% to 7% of the total mass of the raw materials.

[0013] The fused magnesium-rich spinel includes fused magnesium-rich spinel particles and fused magnesium-rich spinel fine powder, wherein the particle size composition of the fused magnesium-rich spinel particles is 50% to 70% by mass of 0.6-0.2 mm and 30% to 50% by mass of 0.2-0.1 mm, the particle size of the fused magnesium-rich spinel fine powder is 320 mesh to 0 mm, and the magnesium oxide content of the fused magnesium-rich spinel is greater than 50%; in the high-temperature ceramic phase forming agent, the particle size of the magnesium-aluminum spinel micropowder is ≤5μ, the particle size of the calcined alumina is less than 5μ, the particle size of the titanium dioxide is less than 2μ, and the particle size of the cerium oxide is less than 2μ; the graphite adopts 199 flake graphite with a particle size of 80-100 mesh and a carbon content of greater than 99%; the particle size of silicon nitride is 200 mesh to 0; the particle size of the metallic silicon powder is 200 mesh to 0; and the particle size of the boron carbide is 320 mesh to 0.

[0014] A method for preparing a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer, comprising mixing, low-pressure prefabrication, high-pressure molding, drying, firing, processing, glazing, drying and packaging processes; the details are as follows:

[0015] 1) Mixing: The stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are mixed separately; the raw materials are weighed according to the ratio and added into a mixer, first dry-mixed for more than 3 minutes, then the liquid phenolic resin is added and wet-mixed for more than 17 minutes, the mixed mud is dried with hot air at 70-100° C. for more than 5 minutes, and after the volatile matter of the mud is dried to the set molding value, the stopper rod body blank, the lightweight porous separation layer blank and the ultra-low carbon anti-erosion layer blank are obtained and set aside;

[0016] 2) Low-pressure molding: Add the lightweight porous partition layer blank into the prefabricated mold, seal it after compaction, and press it in a cold isostatic press at a molding pressure of 10 to 30 MPa to obtain a partition layer prefabricated part;

[0017] 3) High-pressure forming: the stopper rod body blank is added into the combined forming mold and vibrated, and then the separation layer preform and the ultra-low carbon composite layer blank are placed at the position corresponding to the rod head, and a cold isostatic press is used for pressure forming at a forming pressure of 90-120 MPa to obtain a stopper rod forming blank;

[0018] 4) Drying: Send the stopper rod forming blank into a drying kiln for drying. The heating rate during drying is 10-15°C / h, the temperature is raised to 230-260°C, and the temperature is kept for 4-6 hours;

[0019] 5) Firing: The dried stopper rod blank is placed in a sealed can and fired in a high-temperature firing kiln under a reducing atmosphere to form a ceramic bonding phase. The firing temperature is 950°C to 1100°C, the heating rate is 45 to 50°C / h, and the temperature is kept for 3 to 5 hours to obtain a stopper rod blank.

[0020] 6) Processing: The fired stopper rod blank is processed into the finished product size by a CNC lathe to obtain a stopper rod product;

[0021] 7) Glazing and drying: a layer of anti-oxidation coating is evenly applied on the surface of the processed stopper rod product, the coating thickness is 0.5-1.2mm, and the glazed stopper rod product is then dried in a drying furnace, the drying furnace heating rate is 15-30℃ / h, the temperature is raised to 180-200℃, and the heat preservation time is 3-5h;

[0022] 8) Inspection and packaging: After the stopper rod is dried and inspected, it is considered a finished stopper rod and is packaged and put into storage.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The pre-embedded multi-layer gradient composite process is adopted, and the stopper rod body and the ultra-low carbon anti-erosion layer are weakly combined by a low-expansion lightweight porous separation layer, so that the stopper rod body and the ultra-low carbon anti-erosion layer are structurally and functionally separated to form a multi-layer gradient composite structure consisting of the stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer; compared with the existing stopper rod with the ultra-low carbon composite layer directly composited at the rod head, the interface structural stress is effectively eliminated, the crack and peeling problems of the ultra-low carbon composite layer caused by the interface structural stress are reduced, the heat shock resistance of the stopper rod head during use is greatly improved, and the reliability and stability of the stopper rod are enhanced.

[0025] (2) The ultra-low carbon erosion-resistant layer is made of ceramic-toughened ultra-low carbon magnesium-rich spinel material with excellent erosion resistance and thermal shock resistance. It can flexibly cope with erosion under various steel casting conditions and significantly improve the application range and service life of the stopper rod. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the weak phase composite ceramic toughened ultra-low carbon layer long life plug rod of the present invention.

[0027] Figure 2 It is a schematic diagram of the lightweight porous separation layer low-pressure prefabricated component of the present invention.

[0028] In the figure: 1. Rod body 2. Lightweight porous separator layer 3. Ultra-low carbon composite layer DETAILED DESCRIPTION

[0029] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings:

[0030] like Figure 1 , Figure 2 As shown, the present invention describes a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer, and the rod head portion of the long-life stopper rod is a composite structure consisting of a stopper rod body, a lightweight porous separation layer and an ultra-low carbon anti-erosion layer; the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are arranged on the outside of the rod head of the stopper rod body in sequence from the inside to the outside, and the stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are integrally formed by pressure; the stopper rod body is made of aluminum carbon material, and the rod head is divided into a cone structure; the lightweight porous separation layer is a cone-cap shaped structure matched with the rod head portion, and adopts a lightweight porous material; the ultra-low carbon anti-erosion layer is a cone-cap shaped structure matched with the lightweight porous separation layer, and adopts an ultra-low carbon magnesium-rich spinel material with a high-temperature ceramic phase.

[0031] The lightweight porous separation layer has a thickness of 2 to 5 mm and a height of 30 to 60 mm.

[0032] The ultra-low carbon anti-erosion layer has a thickness of 6 to 12 mm and a height of 50 to 90 mm.

[0033] The lightweight porous separation layer is made of low-expansion lightweight hollow sphere material, and is composed of the following raw materials by mass percentage: 81% to 90% lightweight spinel hollow spheres, 2% to 4% graphite, 1% to 5% ceramic powder, 1% to 3% metal silicon powder, and 3% to 7% polypropylene fine powder; in addition, liquid phenolic resin accounts for 3% to 6% of the total mass of the raw materials.

[0034] The particle size composition of the lightweight spinel hollow spheres is 50% to 70% by mass of 0.5 to 0.3 mm and 30% to 50% by mass of 0.3 to 0 mm, and the alumina content is ≥75%; the graphite uses 598 flake graphite powder with a particle size of 30 to 50 meshes and a carbon content of ≥98%; the particle size of the ceramic powder is 200 mesh to 0; the particle size of the metal silicon powder is 200 mesh to 0; and the particle size of the polypropylene fine powder is 120 mesh to 0.

[0035] The raw materials of the ultra-low carbon anti-erosion layer are composed of fused magnesium-rich spinel and a high-temperature ceramic phase former, with liquid phenolic resin added; in terms of mass percentage, the fused magnesium-rich spinel accounts for 70% to 88%; the high-temperature ceramic phase former includes: 3% to 6% magnesium-aluminum spinel powder, 2% to 5% calcined alumina, 1% to 3% titanium dioxide, 1% to 3% cerium oxide, 3% to 5% graphite, 1% to 3% silicon nitride, 1% to 4% metallic silicon powder, and 0% to 1% boron carbide; the liquid phenolic resin accounts for 4% to 7% of the total mass of the raw materials.

[0036] The fused magnesium-rich spinel includes fused magnesium-rich spinel particles and fused magnesium-rich spinel fine powder, wherein the particle size composition of the fused magnesium-rich spinel particles is 50% to 70% by mass of 0.6-0.2 mm and 30% to 50% by mass of 0.2-0.1 mm, the particle size of the fused magnesium-rich spinel fine powder is 320 mesh to 0 mm, and the magnesium oxide content of the fused magnesium-rich spinel is greater than 50%; in the high-temperature ceramic phase forming agent, the particle size of the magnesium-aluminum spinel micropowder is ≤5μ, the particle size of the calcined alumina is less than 5μ, the particle size of the titanium dioxide is less than 2μ, and the particle size of the cerium oxide is less than 2μ; the graphite adopts 199 flake graphite with a particle size of 80-100 mesh and a carbon content of greater than 99%; the particle size of silicon nitride is 200 mesh to 0; the particle size of the metallic silicon powder is 200 mesh to 0; and the particle size of the boron carbide is 320 mesh to 0.

[0037] The method for preparing a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer of the present invention comprises mixing, low-pressure prefabrication, high-pressure molding, drying, firing, processing, glazing, drying and packaging processes; the details are as follows:

[0038] 1) Mixing: The stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are mixed separately; the raw materials are weighed according to the ratio and added into a mixer, first dry-mixed for more than 3 minutes, then the liquid phenolic resin is added and wet-mixed for more than 17 minutes, the mixed mud is dried with hot air at 70-100° C. for more than 5 minutes, and after the volatile matter of the mud is dried to the set molding value, the stopper rod body blank, the lightweight porous separation layer blank and the ultra-low carbon anti-erosion layer blank are obtained and set aside;

[0039] 2) Low-pressure molding: Add the lightweight porous partition layer blank into the prefabricated mold, seal it after compaction, and press it in a cold isostatic press at a molding pressure of 10 to 30 MPa to obtain a partition layer prefabricated part;

[0040] 3) High-pressure forming: the stopper rod body blank is added into the combined forming mold and vibrated, and then the separation layer preform and the ultra-low carbon composite layer blank are placed at the position corresponding to the rod head, and a cold isostatic press is used for pressure forming at a forming pressure of 90-120 MPa to obtain a stopper rod forming blank;

[0041] 4) Drying: Send the stopper rod forming blank into a drying kiln for drying. The heating rate during drying is 10-15°C / h, the temperature is raised to 230-260°C, and the temperature is kept for 4-6 hours;

[0042] 5) Firing: The dried stopper rod blank is placed in a sealed can and fired in a high-temperature firing kiln under a reducing atmosphere to form a ceramic bonding phase. The firing temperature is 950°C to 1100°C, the heating rate is 45 to 50°C / h, and the temperature is kept for 3 to 5 hours to obtain a stopper rod blank.

[0043] 6) Processing: The fired stopper rod blank is processed into the finished product size by a CNC lathe to obtain a stopper rod product;

[0044] 7) Glazing and drying: a layer of anti-oxidation coating is evenly applied on the surface of the processed stopper rod product, the coating thickness is 0.5-1.2mm, and the glazed stopper rod product is then dried in a drying furnace, the drying furnace heating rate is 15-30℃ / h, the temperature is raised to 180-200℃, and the heat preservation time is 3-5h;

[0045] 8) Inspection and packaging: After the stopper rod is dried and inspected, it is considered a finished stopper rod and is packaged and put into storage.

[0046] The long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer described in the present invention adopts a pre-embedded multi-layer gradient composite process. A low-pressure preform of a low-expansion, low-strength lightweight porous material is first embedded in a set position in the flow control area of ​​the rod head, and then a lightweight porous separation layer is formed after high-pressure one-piece molding. The lightweight porous separation layer is used as a separation layer between the stopper rod body and the ultra-low carbon anti-erosion layer, thereby achieving the purpose of weak bonding between the stopper rod body and the ultra-low carbon anti-erosion layer, and finally forming a multi-layer gradient composite structure of the stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer, which effectively eliminates the interface structural stress at the rod head composite structure.

[0047] In order to form an effective stress absorption buffer layer and achieve weak bonding, the separation layer between the stopper rod body and the ultra-low carbon erosion resistance layer is preferably made of low-expansion, low-strength lightweight spinel hollow spheres, with phenolic resin as a binder, ceramic powder as a sintering agent, and polypropylene fine powder as a pore-forming agent. Low-pressure molding is used to prefabricate a 2-5 mm thick separation layer preform.

[0048] In order to adapt to different steel casting conditions and meet the requirements of various types of highly erosive steel and long life, the present invention has developed a ceramic toughened ultra-low carbon magnesium-rich spinel material for use as an ultra-low carbon anti-erosion layer. By adding a high-temperature ceramic phase former, an ultra-low carbon anti-erosion layer with excellent erosion resistance and thermal shock resistance is obtained, and its thickness ranges from 6 to 12 mm and its height ranges from 50 to 90 mm.

[0049] The ultra-low carbon anti-erosion layer of the present invention is made of ceramic toughened ultra-low carbon magnesium-rich spinel material, which is composed of the following raw materials in mass percentage: 70% to 88% of fused magnesium-rich spinel; high-temperature ceramic phase former (including 3% to 6% of magnesium-aluminum spinel micropowder, 2% to 5% of calcined alumina, 1% to 3% of titanium dioxide, 1% to 3% of cerium oxide; 3% to 5% of graphite, 1% to 3% of silicon nitride, 1% to 4% of metallic silicon powder, and 0% to 1% of boron carbide), plus liquid phenolic resin accounting for 4% to 7% of the total mass of the above raw materials.

[0050] Preferably, the fused magnesium-rich spinel includes fused magnesium-rich spinel particles and fused magnesium-rich spinel fine powder, wherein the particle size composition of the fused magnesium-rich spinel particles is 0.6-0.2 mm, which accounts for 50%-70% by mass, and 0.2-0.1 mm, which accounts for 30%-50% by mass, and the particle size of the fused magnesium-rich spinel fine powder is 320 mesh-0 mm; the magnesium oxide content of the fused magnesium-rich spinel is greater than 50%; in the high-temperature ceramic phase former, the particle size of the magnesium-aluminum spinel micropowder is ≤5μ, the particle size of the calcined alumina is less than 5μ, the particle size of the titanium dioxide is less than 2μ, and the particle size of the cerium oxide is less than 2μ; the graphite uses 199 flake graphite with a particle size of 80-100 mesh and a carbon content of greater than 99%; the particle size of silicon nitride is 200 mesh-0; the particle size of the metallic silicon powder is 200 mesh-0; and the particle size of the boron carbide is 320 mesh-0.

[0051] The light porous separation layer of the present invention is made of a light porous material with low expansion (preferably light hollow spinel spheres), with a thickness of 2 to 5 mm and a height of 30 to 60 mm. It is composed of the following raw materials by mass percentage: 81% to 90% of light hollow spinel spheres, 2% to 4% of graphite, 1% to 5% of ceramic powder, 1% to 3% of metal silicon powder, and 3% to 7% of polypropylene fine powder. In addition, liquid phenolic resin accounting for 3% to 6% of the total mass of the above raw materials is added.

[0052] Preferably, the particle size composition of the lightweight spinel hollow spheres is 50% to 70% by mass of 0.5 to 0.3 mm and 30% to 50% by mass of 0.3 to 0 mm, and the alumina content is ≥75%; the graphite uses 598 flake graphite powder with a particle size of 30 to 50 mesh and a carbon content of ≥98%; the particle size of the ceramic powder is 200 mesh to 0; the particle size of the metallic silicon powder is 200 mesh to 0; and the particle size of the polypropylene fine powder is 120 mesh to 0.

[0053] The invention discloses a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer, and the preparation process comprises the following processes: mixing → low-pressure forming → high-pressure forming → drying → firing → processing → glazing and drying → packaging.

[0054] The lightweight porous separation layer adopts a pre-embedded production process of prefabrication followed by compounding, that is, the separation layer preform is first produced by low-pressure molding, and then the separation layer preform is embedded in the preset compound position of the rod head, and then high-pressure molded together with the stopper rod body and the ultra-low carbon anti-erosion layer.

[0055] Through the composite process, the rod head is divided into three layers in terms of structure and function: the inner layer is an aluminum-carbon plug rod support, the middle is a 2-5 mm thick lightweight porous separation layer, which mainly plays the role of interface structure stress absorption; the outer layer is a 6-12 mm thick ceramic toughened ultra-low carbon anti-erosion layer, which mainly plays the anti-erosion function during the flow control process.

[0056] The present invention ensures the stability and reliability of the use of the stopper rod head composite structure from two aspects: production process and material design: first, the three functional layers formed by the multi-layer gradient composite process effectively eliminate the problem of strong interface structural stress easily caused by the direct bonding process, that is, a weak bonding is formed between the stopper rod body and the ultra-low carbon anti-erosion layer by using a lightweight porous material, thereby reducing the bonding interface structural stress, and reducing the interface stress accumulation caused by the large difference in thermal expansion performance between the stopper rod body and the ultra-low carbon anti-erosion layer when used at high temperatures, thereby solving the problem of strong structural stress cracks and thermal spalling easily generated at the interface when the stopper rod body and the ultra-low carbon anti-erosion layer are directly bonded; second, by adding a high-temperature ceramic phase formed by adding a specific additive to the ultra-low carbon material, the high-temperature strength, thermal shock resistance and erosion resistance of the ultra-low carbon anti-erosion layer are improved.

[0057] Generally speaking, for refractory materials of the same material, the thinner the product thickness, the smaller the internal stress generated when subjected to thermal shock, and the better the thermal shock resistance of the product. In order to further improve the thermal shock resistance of the ultra-low carbon anti-erosion layer itself, the present invention designs a suitable thickness to ensure that the plug rod head has high erosion resistance and good thermal shock resistance.

[0058] The stopper rod body, ultra-low carbon anti-erosion layer and lightweight porous separator layer are integrally pressed and formed by a cold isostatic press. Among them, the lightweight porous separator layer adopts a pre-embedded production process of prefabrication first and then compounding, that is, the separator layer prefabricated part is first made by low-pressure molding, and then the separator layer prefabricated part is embedded in the preset position of the rod head, and then high-pressure molding is performed together with the stopper rod body and ultra-low carbon anti-erosion layer. The manufacturing process is simple, and finally a rod head composite structure whose shape, thickness of each layer and compound position meet the design requirements is obtained.

[0059] The material of the stopper rod body of the present invention is the aluminum-carbon material conventionally used for stopper rods, which will not be described in detail in the present invention.

[0060] In order to more intuitively embody the present invention, the embodiments of the present invention are further described in conjunction with examples. The following examples are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any technical solution that can be obviously obtained by a person skilled in the art within the technical scope disclosed in the present invention, including simple changes or equivalent replacements, is within the protection scope of the present invention.

[0061] [Example 1]

[0062] This embodiment produces a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer. A pre-embedded multi-layer gradient composite process is used to prefabricate a separation layer of a low-expansion, low-strength lightweight porous material into a set position in the flow control area of ​​the rod head as a separation layer between the stopper rod body and the ultra-low carbon erosion-resistant layer, and then high-pressure integrated molding is performed.

[0063] In this embodiment, the stopper rod body is made of conventional aluminum carbon material.

[0064] The raw material ratio of the lightweight porous separation layer is as follows by mass percentage: lightweight hollow spinel ball 88%, graphite 2.5%, ceramic powder 3.5%, metal silicon powder 1%, polypropylene fine powder 5%, and liquid phenolic resin accounting for 4% of the total mass of the above raw materials.

[0065] The raw material ratio of the ultra-low carbon anti-erosion layer is as follows in percentage by mass: 80% fused magnesium-rich spinel, 4% magnesium-aluminum spinel powder, 3% calcined alumina, 2% titanium dioxide, 2.5% cerium oxide, 4% graphite, 2% silicon nitride, 2% metallic silicon powder, 0.5% boron carbide, and 5% liquid phenolic resin of the total mass of the above raw materials for mixing.

[0066] The production process of long-life stopper rods with weak-phase composite ceramic toughened ultra-low carbon layers is: mixing → low-pressure prefabrication → high-pressure molding → drying → firing → processing → glazing and drying → packaging.

[0067] 1. Mixing: After weighing the raw materials according to the proportion, add them into the mixer and dry mix for 3 minutes, then add the liquid phenolic resin and wet mix for 17 minutes. The mixed clay is dried with hot air at 85℃ for 5 minutes. After the volatile matter of the clay is dried to a suitable molding value, it is used as a blank for standby;

[0068] 2. Low-pressure forming: Add the lightweight porous partition layer blank into the prefabricated mold, seal it after compaction, and press it in a cold isostatic press to obtain a partition layer prefabricated part with a thickness of 3.5 mm. The molding pressure is 25 MPa.

[0069] 3. High-pressure forming: Add the stopper rod body blank into the combined forming mold, place the separation layer preform and the ultra-low carbon anti-erosion layer blank at the predetermined position after vibration compaction, and press-form in a cold isostatic press to obtain the stopper rod forming blank, and the forming pressure is 100MPa.

[0070] 4. Drying: Dry the stopper rod forming blank in a drying kiln at a heating rate of 15℃ / h to 240℃ and keep warm for 4h;

[0071] 5. Firing: Place the dried plug rod forming blank in a sealed can and fire it in a high-temperature firing kiln under a reducing atmosphere to form a ceramic bonding phase. The firing temperature is 1000°C, the heating rate is 50°C / h, and the temperature is kept for 3 hours.

[0072] 6. Processing: According to the size requirements of the product drawing, the fired stopper rod blank is processed by CNC lathe.

[0073] 7. Glazing and drying: A layer of anti-oxidation coating is evenly applied on the surface of the processed stopper rod product, with a coating thickness of 0.8mm. The glazed stopper rod product is then dried in a drying furnace. The drying furnace has a heating rate of 26℃ / h, and the temperature rises to 180℃, and the insulation time is 3h;

[0074] Packaging: The dried stopper rod products can be packaged and stored after passing the inspection.

[0075] [Example 2]

[0076] This embodiment produces a long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer. A pre-embedded multi-layer gradient composite process is used to prefabricate a separation layer of a low-expansion, low-strength lightweight porous material into a set position in the flow control area of ​​the rod head as a separation layer between the stopper rod body and the ultra-low carbon erosion-resistant layer, and then high-pressure integrated molding is performed.

[0077] In this embodiment, the stopper rod body is made of conventional aluminum carbon material.

[0078] The raw material proportions of the lightweight porous separation layer are as follows by mass percentage: lightweight hollow spinel spheres 84%, graphite 3%, ceramic powder 5%, metal silicon powder 2%, polypropylene fine powder 6%, and liquid phenolic resin accounting for 5% of the total mass of the above raw materials.

[0079] The raw material ratio of the ultra-low carbon anti-erosion layer is as follows in percentage by mass: 85% fused magnesium-rich spinel, 5% magnesium-aluminum spinel powder, 1% calcined alumina, 3% titanium dioxide, 2% cerium oxide, 2% graphite, 1% silicon nitride, 1% metallic silicon powder, and 4% liquid phenolic resin of the total mass of the above raw materials for mixing.

[0080] The production process of long-life stopper rods with weak-phase composite ceramic toughened ultra-low carbon layers is: mixing → low-pressure prefabrication → high-pressure molding → drying → firing → processing → glazing and drying → packaging.

[0081] 1. Mixing: After weighing the raw materials according to the proportion, add them into the mixer and dry mix for 3 minutes, then add the liquid phenolic resin and wet mix for 17 minutes. The mixed clay is dried with 90℃ hot air for 5 minutes. After the volatile matter of the clay is dried to a suitable molding value, it is used as a blank for standby;

[0082] 2. Low-pressure forming: Add the lightweight porous partition layer blank into the prefabricated mold, seal it after compaction, and press it in a cold isostatic press to obtain a partition layer prefabricated part with a thickness of 4 mm. The molding pressure is 20 MPa.

[0083] 3. High-pressure forming: Add the stopper rod body blank into the combined forming mold, place the separation layer preform and the ultra-low carbon anti-erosion layer blank at the predetermined position after compaction, and press-form in a cold isostatic press to obtain the stopper rod forming blank, with a forming pressure of 110 MPa.

[0084] 4. Drying: Dry the stopper rod forming blank in a drying kiln at a heating rate of 15℃ / h to 240℃ and keep warm for 4h;

[0085] 5. Firing: Place the dried plug rod forming blank in a sealed can and fire it in a high-temperature firing kiln under a reducing atmosphere to form a ceramic bonding phase. The firing temperature is 1050°C, the heating rate is 50°C / h, and the temperature is kept for 3 hours.

[0086] 6. Processing: According to the size requirements of the product drawing, the fired stopper rod blank is processed by CNC lathe.

[0087] 7. Glazing and drying: A layer of anti-oxidation coating is evenly applied on the surface of the processed stopper rod product, with a coating thickness of 1.0 mm. The glazed stopper rod product is then dried in a drying furnace. The drying furnace is heated at a rate of 18°C / h, and the temperature is raised to 180°C for 3 hours;

[0088] Packaging: The dried stopper rod products can be packaged and stored after passing the inspection.

[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A long-life stopper rod with a weak phase composite ceramic toughened ultra-low carbon layer, characterized in that: The rod head part of the long-life stopper rod is a composite structure composed of a stopper rod body, a lightweight porous separation layer and an ultra-low carbon anti-erosion layer; the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are arranged on the outside of the rod head of the stopper rod body in sequence from the inside to the outside, and the stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are integrally formed by pressure; the stopper rod body is made of aluminum carbon material, and the rod head is divided into a cone structure; the lightweight porous separation layer is a cone-cap shaped structure matched with the rod head part, and is made of lightweight porous material; the ultra-low carbon anti-erosion layer is a cone-cap shaped structure matched with the lightweight porous separation layer, and is made of ultra-low carbon magnesium-rich spinel material with a high-temperature ceramic phase.

2. A long-life stopper rod with a weak phase composite ceramic toughened ultra-low carbon layer according to claim 1, characterized in that: The lightweight porous separation layer has a thickness of 2 to 5 mm and a height of 30 to 60 mm.

3. The long-life stopper rod with a weak phase composite ceramic toughened ultra-low carbon layer according to claim 1, characterized in that: The ultra-low carbon anti-erosion layer has a thickness of 6 to 12 mm and a height of 50 to 90 mm.

4. The long-life stopper rod with a weak phase composite ceramic toughened ultra-low carbon layer according to claim 1, characterized in that: The lightweight porous separation layer is made of low-expansion lightweight hollow sphere material, and is composed of the following raw materials by mass percentage: 81% to 90% lightweight spinel hollow spheres, 2% to 4% graphite, 1% to 5% ceramic powder, 1% to 3% metal silicon powder, and 3% to 7% polypropylene fine powder; in addition, liquid phenolic resin accounts for 3% to 6% of the total mass of the raw materials.

5. A long-life stopper rod with a weak phase composite ceramic toughened ultra-low carbon layer according to claim 4, characterized in that: The particle size composition of the lightweight spinel hollow spheres is 50% to 70% by mass of 0.5 to 0.3 mm and 30% to 50% by mass of 0.3 to 0 mm, and the alumina content is ≥75%; the graphite uses 598 flake graphite powder with a particle size of 30 to 50 meshes and a carbon content of ≥98%; the particle size of the ceramic powder is 200 mesh to 0; the particle size of the metal silicon powder is 200 mesh to 0; and the particle size of the polypropylene fine powder is 120 mesh to 0.

6. The long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer according to claim 1, characterized in that: The raw materials of the ultra-low carbon anti-erosion layer are composed of fused magnesium-rich spinel and high-temperature ceramic phase forming agent, and liquid phenolic resin is added; By mass percentage, fused magnesium-rich spinel 70% to 88%; The high-temperature ceramic phase former includes: 3% to 6% magnesium aluminum spinel powder, 2% to 5% calcined aluminum oxide, 1% to 3% titanium dioxide, 1% to 3% cerium oxide, 3% to 5% graphite, 1% to 3% silicon nitride, 1% to 4% metallic silicon powder, and 0 to 1% boron carbide; the liquid phenolic resin accounts for 4% to 7% of the total mass of the raw materials.

7. A long-life stopper rod with a weak-phase composite ceramic toughened ultra-low carbon layer according to claim 6, characterized in that: The fused magnesium-rich spinel includes fused magnesium-rich spinel particles and fused magnesium-rich spinel fine powder, wherein the particle size composition of the fused magnesium-rich spinel particles is 50% to 70% by mass of 0.6-0.2 mm and 30% to 50% by mass of 0.2-0.1 mm, the particle size of the fused magnesium-rich spinel fine powder is 320 mesh to 0 mm, and the magnesium oxide content of the fused magnesium-rich spinel is greater than 50%; in the high-temperature ceramic phase forming agent, the particle size of the magnesium-aluminum spinel micropowder is ≤5μ, the particle size of the calcined alumina is less than 5μ, the particle size of the titanium dioxide is less than 2μ, and the particle size of the cerium oxide is less than 2μ; the graphite adopts 199 flake graphite with a particle size of 80-100 mesh and a carbon content of greater than 99%; the particle size of silicon nitride is 200 mesh to 0; the particle size of the metallic silicon powder is 200 mesh to 0; and the particle size of the boron carbide is 320 mesh to 0.

8. A method for preparing a long-life stopper rod having a weak-phase composite ceramic toughened ultra-low carbon layer as claimed in any one of claims 1 to 7, characterized in that: Including mixing, low-pressure prefabrication, high-pressure molding, drying, firing, processing, glazing drying and packaging processes; the details are as follows: 1) Mixing: The stopper rod body, the lightweight porous separation layer and the ultra-low carbon anti-erosion layer are mixed separately; the raw materials are weighed according to the ratio and added into a mixer, first dry-mixed for more than 3 minutes, then the liquid phenolic resin is added and wet-mixed for more than 17 minutes, the mixed mud is dried with hot air at 70-100° C. for more than 5 minutes, and after the volatile matter of the mud is dried to the set molding value, the stopper rod body blank, the lightweight porous separation layer blank and the ultra-low carbon anti-erosion layer blank are obtained and set aside; 2) Low-pressure molding: Add the lightweight porous partition layer blank into the prefabricated mold, seal it after compaction, and press it in a cold isostatic press at a molding pressure of 10 to 30 MPa to obtain a partition layer prefabricated part; 3) High-pressure forming: the stopper rod body blank is added into the combined forming mold and vibrated, and then the separation layer preform and the ultra-low carbon composite layer blank are placed at the position corresponding to the rod head, and a cold isostatic press is used for pressure forming at a forming pressure of 90-120 MPa to obtain a stopper rod forming blank; 4) Drying: Send the stopper rod forming blank into a drying kiln for drying. The heating rate during drying is 10-15°C / h, the temperature is raised to 230-260°C, and the temperature is kept for 4-6 hours; 5) Firing: The dried stopper rod blank is placed in a sealed can and fired in a high-temperature firing kiln under a reducing atmosphere to form a ceramic bonding phase. The firing temperature is 950°C to 1100°C, the heating rate is 45 to 50°C / h, and the temperature is kept for 3 to 5 hours to obtain a stopper rod blank. 6) Processing: The fired stopper rod blank is processed into the finished product size by a CNC lathe to obtain a stopper rod product; 7) Glazing and drying: a layer of anti-oxidation coating is evenly applied on the surface of the processed stopper rod product, the coating thickness is 0.5-1.2mm, and the glazed stopper rod product is then dried in a drying furnace, the drying furnace heating rate is 15-30℃ / h, the temperature is raised to 180-200℃, and the heat preservation time is 3-5h; 8) Inspection and packaging: After the stopper rod is dried and inspected, it is considered a finished stopper rod and is packaged and put into storage.

Citation Information

Patent Citations

  • Long-life monoblock stopper made from spinel materials

    CN105418094A

  • Bottom pouring furnace stopper rod and preparation method thereof

    CN108947550A

  • Integrated stopper rod used for continuous casting

    CN201572910U

  • High-performance stopper rod

    CN217647482U

  • Refractory shape having an external layer capable of forming a layer impermeable to gases and process for its preparation

    US5691061A